Identifikasi Sifat Fisik Lahan Gambut Rasau Jaya III Kabupaten Kubu Raya untuk Pengembangan Jagung - Denah Suswati; Bambang Hendro; Shiddieq Shiddieq; Didik Indradewa (Fakultas Pertanian Universitas Tanjungpura, 2011)
This research was aimed to identify the physical properties of land which includes the level of maturity and the thickness of peat, soil color, texture, structure, consistency, drainage, groundwater depth, soil effective depth, the depth of sulfidik, and the maturity of soil (n-value) as well as recommending the management of soil to support the development maize on peat land. The research was carried out in the Rasau Jaya III area Kubu Raya Regency, with an area of 2,490 Ha. The Soil physical analysis done in the laboratory of Soil Physics and Conservation the Faculty of Agriculture Tanjungpura University.